The Legal support of social responsibility of agribusiness entities of Ukraine - Korniyenko , Ganna (DIXI, 2021)
Corporate social responsibility is a current issue for every European country, due to the implementation of the United Nations Guiding Principles on Business and Human Rights. For Ukrainian agribusiness, the issue of social responsibility becomes especially important as Ukraine is at the initial stage of formation of the land market. It is expected that investors will take part in the social development of rural areas. So, this must be taken into account when planning agrarian business in Ukraine. At the same time, the legal regulation of corporate social responsibility is still insufficiently developed, which determines the relevance of the topic of the article.
Keywords: agrarian law; sustainable development; social responsibility; agrarian production; agribusiness